A case study investigating the role of the anterior temporal lobes in general semantics and semantics specific to persons, emotions and social conceptual knowledge. Issue 3 (30th November 2020) - Foley, Jennifer A.; Hyare, Harpreet; Rees, Jeremy H.; Caine, Diana
Abstract : The role of the anterior temporal lobes (ATLs) in semantic representation remains still much debated. Long thought to support domain‐general semantic processing, recent accounts have alternatively suggested that they may be preferentially involved in the processing of person‐related semantic knowledge. Several studies have supported such a distinction, but few have either examined both types of semantic processing together, or considered the role of potentially important confounding variables. Here, we address these issues by investigating both domain‐general and person‐specific semantic processing in a patient with focal ATL damage. The patient presents with dense anterograde and retrograde amnesia. Performance was impaired on tests of general semantic knowledge, but most striking deficits were for person‐related semantics, including recognition and identification, knowledge of emotions and social conceptual knowledge. This unique case provides compelling evidence that, in addition to the role in general semantic knowledge, the ATLs are critical for person‐related semantics.